Structural characterization and antioxidant activities of polysaccharides from Angelica dahurica as extracted by optimized ultrasonic-assisted method - Xinyue Pang; Yongshuai Jing; Pengyue Li; Xiaoyue Qiu; Yuguang Zheng; Qian Wang; Lanfang Wu (International Journal of Food Properties, 2022)
The study aimed to select the best extraction technology of Angelica dahurica polysaccharides (ADP), characterize its structure, and antioxidant activity. On the basis of the single-factor experiment result, the ultrasonic-assisted extraction (UAE) of ADP was ameliorate using the response surface method. The optimal conditions were: extraction time 32 min, extraction temperature 74°C, ratio of water to material 19 mL/g, extraction power 270 W. The practical extraction rate was 11.21 ± 0.12% (g/g). C-1: Not clear?? g/s??? ADP was purified by column chromatography, and then three polysaccharide fractions (ADP-H, ADP-0.1 and ADP-0.3) were obtained using DEAE-Cellulose 52. The ADP was mainly composed of D-Mannose, D-Glucose, D-Galactose, L-Arabinose, the ADP-H was mainly composed of D-Mannose, D-Glucose, D-Galactose, L-Arabinose, the ADP-0.1 was mainly composed of D-Mannose, D-Galacturonic acid, D-Glucose, D-Galactose, L-Arabinose, and the ADP-0.3 was mainly composed of D-Mannose, L-Rhamnose, D-Galacturonic acid, D-Galactoe, L-Arabinose. The molecular weights of ADP-H, ADP-0.1 and ADP-0.3 were 1.01 × 104 Da, 1.45 × 107 Da and 6.96 × 106 Da. In addition, the purified polysaccharides have certain scavenging ability of DPPH free radical, hydroxyl free radical and ferric reducing power, which can be used as natural products of antioxidants.